2020
DOI: 10.3389/fonc.2020.570733
|View full text |Cite
|
Sign up to set email alerts
|

miR-550a-5p Functions as a Tumor Promoter by Targeting LIMD1 in Lung Adenocarcinoma

Abstract: Lung adenocarcinoma accounts for half of all lung cancer cases in most countries. Mounting evidence has demonstrated that microRNAs play important roles in cancer progression, and some of them can be identified as potential biomarkers. This study aimed to explore the role of miR-550a-5p, a lung adenocarcinoma-associated mature microRNA screened out from the TCGA database via R-studio and Perl, with abundant expression in samples and with 5-year survival prognosis difference, as well as having not been studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Similar to our results, miR-550a-5p has been reported to function as a tumor promoter in colorectal cancer and lung adenocarcinoma [ 53 , 54 ]. However, currently no literature report elucidates the biological function of miR-550a-5p in breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our results, miR-550a-5p has been reported to function as a tumor promoter in colorectal cancer and lung adenocarcinoma [ 53 , 54 ]. However, currently no literature report elucidates the biological function of miR-550a-5p in breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…For example, interference of miR‐324‐3p impeded lung cancer progression via regulating ALX4 to inactivate the MAPK pathway 17 . Furthermore, upregulation of miR‐550a‐5p contributed to the growth of lung adenocarcinoma by suppressing LIMD1 18 . Additionally, Xiao et al suggested that miR‐7‐5p was conspicuously decreased in NSCLC, and its overexpression hindered NSCLC tumorigenesis through negatively regulating NOVA2 19 .…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, Limd1 (LIM domain-containing protein 1) is a member of the Zyxin proteins and is widely expressed in human tissues. Several previous studies have suggested the suppressor role of Limd1 in tumor diseases [ 39 ]. In cardiovascular disease, Limd1 has been reported to be functionally closely related to cardiac fibroblasts [ 40 ].…”
Section: Discussionmentioning
confidence: 99%